National mapping of schistosomiasis, soil-transmitted helminthiasis and anaemia in Yemen: Towards better national control and elimination. - Nur Alia Johari; Dhekra Amin Annuzaili; Hani Farouk El-Talabawy; Maryam Ba-Break; Abdulsalam M Al-Mekhlafi; Samira Al-Eryani; Abdulhakim Ali Alkohlani; Albis Francesco Gabrielli; Riadh Ben-Ismail; Sami Alhaidari; Adel Muaydh; Rasheed Alshami; et al. (PLoS Neglected Tropical Diseases, 2022)
Background Schistosomiasis (SCH) and soil-transmitted helminthiasis (STH) are known to be endemic in Yemen. However, the distribution of both diseases had not previously been assessed by a well-structured national mapping study covering all governorates. The main aim of this study was, therefore, to map the prevalence of SCH and STH in Yemen in order to better inform implementation of effective national control and elimination interventions. The assessment of the distribution of anaemia was also included as a well-known consequence of infection with both SCH and STH. Secondarily, the study aimed to provide a broad indication of the impact of large-scale treatment on the distribution of infection. Methodology and principal findings To achive these aims, 80,432 children (10-14 years old) from 2,664 schools in 332 of Yemen's 333 districts were included, in 2014, into this national cross-sectional survey. Countrywide, 63.3% (210/332) and 75.6% (251/332) of districts were found to be endemic for SCH and STH respectively. More districts were affected by intestinal than urogenital SCH (54.2% and 31.6% respectively). SCH infection was mostly mild and moderate, with no districts reporting high infection. One quarter (24.4%) of Yemeni districts had high or moderate levels of Ascaris lumbricoides infection. Infection with Trichuris trichiura was the second most common STH (44.9% of districts infected) after A. lumbricoides (68.1%). Hookworm was the least prevalent STH (9.0%). Anaemia was prevalent in 96.4% of districts; it represented a severe public health problem (prevalence ≥ 40%) in 26.5% of districts, and a mild to moderate problem in two thirds of the districts (33.7% and 36.1% respectively). Conclusion This study provided the first comprehensive mapping of SCH, STH, and anaemia across the country. This formed the basis for evaluating and continuing the national control and elimination programme for these neglected tropical diseases in Yemen.